Comparative Law Of Cartels Between Indonesia And Japan (Review Of Act No. 5 Of 1999 Concerning Prohibition Of Monopolistic Practices And Unfair Business Competition And The Act Concerning Prohibition Of Private Monopoly And Maintenance Of Fair Trade) - Recca Ayu Hapsari (International Multidiciplinary Conference on Social Sciences (IMCoSS), 2015)
The decision of Act No. 5 of 1999 concerning Prohibition of Monopolistic Practices and Unfair Business Competition is expected to create healthy competition and efficient markets. Indonesia as a country has a new Anti-Monopoly Act need to learn the countries who first implemented similar legislation. The legal reform is important, because at present the current Asian countries have been in the process of legal reform a new competition and firm. It research about comparative law in regarding the form and type of cartel, the scope of proving cartel, and than sanctions imposed from the both of Act No. 5 of 1999 (Indonesia Anti-Monopoly Act) and Act No. 54 of 14 April 1947(Japan Anti-Monopoly Act).  Japan Anti-Monopoly Act in the scope of forms and types of cartels is more clearly because in directly it is expressed as a violation of antitrust laws and as per se rule. While the Act No. 5 of 1999 must be proven in monopolistic practices and unfair business competition, then it see as reasonable restraint.